The future of inpatient diabetes management: glucose as the sixth vital sign. Issue 2 (March 2013) - Rendell, Marc; Saiprasad, Saraswathi; Trepp-Carrasco, Alejandro G; Drincic, Andjela
Diabetes is an ever increasing health problem in our society. Due to associated small and large vessel conditions, patients with diabetes are two- to four-fold more likely to require hospitalization than nondiabetic individuals. Furthermore, hyperglycemia in hospitalized patients results in increased susceptibility to wound infections, worse outcomes postcardiac and cerebrovascular events, longer hospital length of stay and increased inpatient mortality. Several studies suggest that tight control of glucose levels yields improvement in these factors. Conversely, other studies have suggested increased mortality after tight glucose management, perhaps as a result of an increased incidence of hypoglycemic events. The most reasonable approach to control of hyperglycemia is to normalize glucose levels as much as possible without triggering hypoglycemia. In the hospital, insulin therapy of hyperglycemia is preferred due to the ability to flexibly manage glucose levels without side effects associated with many alternative antidiabetic agents. Due to the increasing burden of inpatient diabetes, and the detrimental effects of both hyper and hypoglycemia, the authors predict that blood–glucose levels will become the sixth vital sign to be frequently monitored in hospitalized patients and controlled in a narrow range. The future is in the use of insulin pumps controlled by continuous glucose monitors. This technology is complex and has not yet become standard. The development of future inpatient diabetes care will depend on adaptation of hospital systems to advance the new technology.